Autocatalytic growth of biofunctionalized antibacterial silver nanoparticles. (12th March 2014) - Dhas, Sindhu Priya; John, Shiny Punalur; Mukherjee, Amitava; Chandrasekaran, Natarajan
Abstract Development of eco‐friendly processes for nanosynthesis is gaining importance owing to the widespread application of nanoparticles (NPs). In the present study, we have explained the mechanism and kinetics of bioreduction in the biosynthesis of silver nanoparticles (AgNPs) using aqueous leaf extract of Rhizophora apiculata. Spectrophotometric methods were employed to quantify the bioactive molecules present before and after the reduction process. The results showed that the polyphenols were the main components responsible for the biosynthesis of AgNPs, which was further confirmed by Fourier transform infrared spectroscopy. The kinetics of formation of AgNPs were monitored by time‐resolved spectrophotometric and X‐ray diffraction studies, which revealed that the NP formation is an autocatalytic process with a rate constant of 1.9 × 10−2 Min−1. The NPs were characterized using spectroscopic and microscopic techniques like ultraviolet–visible absorption spectroscopy, dynamic light scattering, transmission electron microscopy, scanning electron microscopy–energy‐dispersive X‐ray spectroscopy, and X‐ray diffraction. The biogenic AgNPs showed substantial inhibitory activity to Proteus mirabilis, Pseudomonas aeruginosa, Escherichia coli, and Staphylococcus aureus with minimum inhibitory concentration values of 2.5, 12.5, 2.5, and 31.25 μg/mL, respectively. The current research provides an insight into the mechanistic aspects of bioreduction and formation of AgNPs.